LUAS PANEN DAN PRODUKSI PADI, JAGUNG, KEDELAI TERHADAP PRODUK DOMESTIK REGIONAL BRUTO PROPINSI Di INDONESIA PADA PROGRAM PENINGKATAN PANGAN PAJALE - Aswin Nasution (Jurnal Bisnis Tani, 2012)
In the period of 2006 - 2015, the production of rice, corn and soybean increased but the government still had to import because the national requirement is still bigger than production, the effort to increase the production is done by UPSUS Pajale. This research was conducted to determine the effect of planting area and production of rice, corn and soybean to provincial PDRB of Indonesia. The results showed that the harvested area of paddy, corn and soybean crops had a strong influence on production at the beginning of the 2015 UPSUS Pajale program but the effect was decreased in 2016. The harvested area of paddy, corn and soybean is not strong in influencing the provincial PDRB in Indonesia, where by simultaneous test and partial test in 2016 the area of harvest of paddy, corn and soybean does not show significant influence to provincial PRDB. Production of paddy, corn and soybeans is also not strong in influencing the PDRB of provinces in Indonesia, where with the simultaneous test in 2016 rice, corn and soybean production show a significant influence on provincial PDRB but with partial test only rice production showing significant influence to PDRB. Rice shows more influence to provincial PDRB compared to corn and soybean. Research suggests that to encourage production of vital harvesting factors is important, but more importantly increase productivity from existing land areas, and improve farming support infrastructure